2010
DOI: 10.1080/10610278.2010.506545
|View full text |Cite
|
Sign up to set email alerts
|

The enantiomeric separation of 4,5-disubstituted imidazoles by HPLC and CE using cyclodextrin-based chiral selectors

Abstract: The enantiomeric separation of a series of fifteen racemic 4,5-disubstituted imidazole compounds was examined by high performance liquid chromatography (HPLC) and capillary electrophoresis (CE). These alkaloid analytes are important precursors for the total synthesis of the natural product calcaridine A and other Leucetta-derived alkaloids. Therefore, the enantiomeric analysis of these analytes is not only important in the production of enantiomerically pure calcaridine A, but also for a better understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…All the compounds studied by HPLC were also investigated by CE using derivatized cyclodextrins as chiral selectors. In a related study, sulfated‐β‐CD was reported as an optimum chiral selector for similar compounds . However, when using sulfated‐β‐CD in this study, no enantiomeric separations was observed in either normal or reverse polarity modes.…”
Section: Resultsmentioning
confidence: 52%
See 4 more Smart Citations
“…All the compounds studied by HPLC were also investigated by CE using derivatized cyclodextrins as chiral selectors. In a related study, sulfated‐β‐CD was reported as an optimum chiral selector for similar compounds . However, when using sulfated‐β‐CD in this study, no enantiomeric separations was observed in either normal or reverse polarity modes.…”
Section: Resultsmentioning
confidence: 52%
“…In a related study, sulfated-b-CD was reported as an optimum chiral selector for similar compounds. 39 However, when using sulfated-b-CD in this study, no enantiomeric separations was observed in either normal or reverse polarity modes. Clearly, this set of alkaloid compounds behave much differently than those studied previously.…”
Section: Ce Analysesmentioning
confidence: 52%
See 3 more Smart Citations